Hut lung : a study of domestically acquired pneumoconiosis in rural women - Grobbelaar, Johannes P (Division of Pulmonology, 2017)
Pneumoconiosis in rural Transkeian women termed "Transkei Silicosis" has been thought to be caused by silica inhaled while grinding maize by traditional methods (Palmer and Daynes, 1967). This study was undertaken to investigate the features and causes of hut lung. The range of clinical, radiologic, histologic, pulmonary physiologic and broncho-alveolar lavage features in patients meeting the following criteria was assessed: i) rural women practising traditional cooking methods ii) with a diffuse nodularity on chest x-ray iii) and lung biopsy evidence of pneumoconiosis iv) and without occupational exposure v) or evidence of active tuberculosis. Smoke and dust levels were measured in rural dwellings during cooking and maize grinding and ground maize and grinding rocks were analysed. 25 patients were studied. 17 were non-smokers, 5 were pipe smokers and 3 smoked 10 or less cigarettes per day. 7 had evidence of previous tuberculosis. The radiological findings ranged from a diffuse fine miliary pattern through coarse nodules with coalescence, to extensive fibrosis resembling PMF. The histologic features revealed simple "anthracosis" in 12, anthracosis with macules in 6 and mixed dust fibrosis in 7, of which 2 had silicotic nodules and 1 PMF. No such findings were observed in the control lung biopsy specimens obtained at post-mortem from city dwelling Xhosa females. Mild to moderate airflow limitation (defined as an FEV1/FVC ratio of < 65% and/or RV> 145% of predicted) was present in 73% while a reduced T'LCO (< 80% predicted) was found in 76% of the patients. Cell numbers and differential counts in BAL fluid were normal but> 80% of the macrophages were heavily laden with inorganic inclusions. The mean smoke level during indoor open fire cooking was 30mg/m³. Respirable dust and quartz concentrations ranging from 3,03 to 5, 82mg/m³ and 0,097 to 0,186mg/m³ respectively were found during hand grinding with sandstone (100% quartz), but were lower (ranging from 2,62 to 3,40mg/m³ and 0,024mg/m³ respectively) when non-quartz containing dolerite was used. Calculated cumulative equivalent time-weighted average respirable dust concentrations were shown to be similar to those found in an average South African gold mine while calculated equivalent respirable quartz concentrations were well below those found in the worst exposed gold miners and well within the recommended threshold limit values of the National Institute for Occupational Safety and Health (NIOSH) and the World Health Organisation (WHO). Respirable quartz exposure alone was not sufficient to explain the changes found. Respirable non-quartz containing nuisance dust and intense smoke exposure were shown to be significant. It was concluded that: i) hut lung can be defined as a domestic pneumoconiosis that occurs in rural women who practise primitive cooking methods ii) hut lung typically occurs in rural maize grinding Transkeian women but can occur in other rural women iii) there is a wide clinical, spectrum radiological and histologic iv) the pulmonary physiological changes are predominantly those of airflow limitation with some CO transfer factor reduction v) cigarette and pipe smoking do not contribute to the aetiology or pulmonary physiological abnormalities vi) the bronchoalveolar lavage features may help differentiate this condition from miliary tuberculosis vi) the aetiology of hut lung is multifactorial with exposure to respirable quartz and non-quartz containing dust together with smoke particles from biomass fuelled fires all playing a significant role while previous tuberculosis may be a contributing factor.